1999
DOI: 10.1016/s0092-8674(00)81016-8
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Protein Folding Is Driven by the Electron Transport System

Abstract: Disulfide bond formation is catalyzed in vivo by DsbA and DsbB. Here we reconstitute this oxidative folding system using purified components. We have found the sources of oxidative power for protein folding and show how disulfide bond formation is linked to cellular metabolism. We find that disulfide bond formation and the electron transport chain are directly coupled. DsbB uses quinones as electron acceptors, allowing various choices for electron transport to support disulfide bond formation. Electrons flow v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
340
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 366 publications
(348 citation statements)
references
References 37 publications
6
340
0
2
Order By: Relevance
“…DsbA concentration was varied between 0 and 40 M, and the reactions were followed by the decrease in DsbA fluorescence at 330 nm. A membrane preparation from an E. coli strain overproducing DsbB was used to catalyze the reaction as described previously (4,35).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…DsbA concentration was varied between 0 and 40 M, and the reactions were followed by the decrease in DsbA fluorescence at 330 nm. A membrane preparation from an E. coli strain overproducing DsbB was used to catalyze the reaction as described previously (4,35).…”
Section: Figmentioning
confidence: 99%
“…DsbA-mediated disulfide bond formation in the periplasm involves oxidation of reduced, newly translocated substrate polypeptides by DsbA, followed by reoxidation of DsbA by the inner membrane protein DsbB. DsbB is in turn reoxidized by molecular oxygen through ubiquinone and terminal cytochrome oxidases (3,4).…”
mentioning
confidence: 99%
“…Disulfides are well known to play an important structural role, contributing to the maintenance of the proper folding in proteins. More recently it was found that the formation of disulfides in proteins also exerts critical regulatory functions: vital mechanisms such as protein import, regulation of signal transduction cascades, regulation of the activity of transcription factors and proper function of the mitochondrial electron transport system rely on disulfide oxidation or reduction [1][2][3][4]. Moreover, the formation of disulfides represents an early, reversible response to oxidative *Corresponding author: mastroberardinopg@upmc.edu.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, under the anaerobic and reducing conditions typical for the growth of strict anaerobes, a different pathway for the disposal of electrons must be imagined. Bader et al (1999) have recently shown that when a strain of E. coli with null mutations in cytochrome bd and bo oxidases was grown under anaerobic conditions in a GasPak Anaerobic System (albeit with no added reducing agent) to avoid interference from trace quantities of oxygen and with glucose as the primary carbon source, the periplasmic indicator protein ÎČ-lactamase was maintained in an oxidized form. This and related data documented that in E. coli growing under anaerobic conditions, the DsbADsbB system shuttles electrons via menaquinone to terminal acceptors such as fumarate.…”
Section: Redox State Of Dnase a In Vivomentioning
confidence: 99%